Analisa Perbandingan Akurasi Dan Efisiensi Pengambilan Titik Elevasi Muka Tanah Menggunakan Google Earth dan GPS (Studi Kasus Jalan Citandui Sta 3+ 00-4 + 250) - Miftah Albani; Elly Tri Pujiastutie (MAJALAH TEKNIK SIMES, 2018)
In this modern age the elevation point can be made easily, for example taking elevation points can use GPS(Global Positioning System) or can also use google earth applications available on the internet. In civilengineering the ground elavation data must be accurate and detailed data. for that whether the above two toolcan be used for accurate and detailed ground elevation point capture.This study aims to determine the accuracy and efficiency of land elevation point taking with google earth andGPS, by comparing the elevation results between the to devices againts theodolite measurement results (T.0)and how the elevation is derived. Beginning with measurement using GPS, google earth done in Citandui streetUrban Village Muara Dua District Kampung Melayu Kota Bengkulu and compare the results of both tools to theresults of theodilite measurement (T.O) the results are closer then it is considered more accurate.From the comparison, it can be concfuded: (I) that the measurement using google carth application is moreaccurate with the average accuracy value of the whole point of the station is 84.82% while the GPS with thepercentage of accuracy is 83.41% 2) based on google earth time more efficient than GPS measuringistrument with efficient percentage value of 74,8%. Based on google carth cost more efficient 89.1% 3) Howto get elevation data using google earth and GPS is quite easy. Using google earth, done in PC or laptop usingpoogle earth application by entering coordinaes of location which have been taken using GPS measuringinstrument, using GP? only need GPS measuring instrument and done location direct research by markingstations (STA) points.